DIELECTRIC SPECTROSCOPIC EVALUATION IN THE EXTREMELY LOW FREQUENCY RANGE OF AN ASPERGILLUS NIGER CULTURE - LINGVAY, Mónika; CARAMITU, Alina-Ruxana; BORȘ, Adriana-Mariana; LINGVAY, Iosif (Studia Universitatis Babeș-Bolyai Chemia, 2019)
By using the dielectric spectroscopy technique in the extremely low frequency (1–200Hz) range, dielectric loss tgδ was determined on both Aspergillus niger cultures in different growth stages and autoclaved biomass compared to the Czapex-Dox culture medium with sterile sucrose. Experimental results have shown that living and sterile matter samples have different dielectric characteristics. In sterile probes, the evolutionary functions of tgδ depending on frequency are continuous, specific to α-relaxation governed by DC electrical conductivity. In living matter samples, the function of dielectric losses tgδ, depending on frequency, show several discontinuities that indicate the existence of some processes in which, at those frequencies, the number of charge carriers from investigated living matter is changing. It has also been found that the package of active processes differs depending on the growth stage of Aspergillus niger.